HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEJADIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SEBULU 1 KECAMATAN SEBULU, KABUPATEN KUTAI KARTANEGARA - RAHMI, TASYA ALIYA; RUSDI, RUSDI; YULIAWATI , RATNA (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
High Blood Pressure or Hypertension is an increase in blood pressure in the arteries. Hypertension as a heterogeneous group of diseases can attack anyone from various age, social and economic groups. The aim of this research is to determine whether there is a relationship between knowledge and attitudes regarding the incidence of hypertension in the work area of Sebulu 1 Community Health Center, Sebulu District. The type of research used is Cross Sectional. The sample in this study was 68 people suffering from hypertension in the working area of the Sebulu 1 Community Health Center, with samples taken using a purposive sampling technique. Analyzed using the Chi Square test. The results of the research obtained a frequency distribution of knowledge regarding the incidence of hypertension, as many as 68 respondents, 14 respondents (20.6%) had poor knowledge of hypertension, 26 respondents (38.2%) had moderate knowledge of hypertension, and 28 respondents (41,2%) had good knowledge of hypertension (2%). Attitudes regarding the incidence of hypertension, as many as 68 respondents, attitudes towards hypertension were poor, there were 3 respondents (4.4%), attitudes towards moderate hypertension were 60 respondents (88.2%) and knowledge regarding hypertension was good as many as 5 respondents (7.4%). Based on the analysis tests that have been carried out, significant results were obtained with a p value <0.001, so the distribution shows that the relationship between knowledge and attitudes and the incidence of hypertension has a significant relationship. ABSTRAKTekanan Darah Tinggi atau Hipertensi adalah suatu peningkatan tekanan darah di dalam arteri. Hipertensi sebagai penyakit heterogeneous group of disease bisa menyerang siapa saja dari berbagai kelompok umur, sosial dan ekonomi. Tujuan penelitian ini adalah untuk mengetahui apakah ada hubungan pengetahuan dan sikap adanya kejadian hipertensi di wilayah kerja Puskesmas Sebulu 1 Kecamatan Sebulu. Jenis penelitian yang digunakan adalah Cross Sectional. Sampel pada penelitian ini adalah penderita hipertensi di wilayah kerja puskesmas sebulu 1 berjumlah 68 orang dengan pengambilan sampel dengan menggunakan teknik Purposive sampling. Dianalisis dengan menggunakan uji Chi Square. Hasil penelitian diperoleh distribusi frekuensi Pengetahuan dengan kejadian hipertensi, sebanyak 68 responden pengetahuan dengan hipertensi buruk sebanyak 14 responden (20,6%), pengetahuan dengan hipertensi sedang sebanyak 26 responden (38,2%) dan pengetahuan dengan hipertensi baik sebanyak 28 responden (41,2%). Sikap dengan kejadian hipertensi, sebanyak 68 responden sikap dengan hipertensi buruk sebanyak 3 responden (4,4%), sikap dengan hipertensi sedang sebanyak 60 responden (88,2%) dan pengetahuan dengan hipertensi baik sebanyak 5 responden (7,4%).Berdasarkan Uji analisis yang telah dilakukan didapatkan hasil siginifikan dengan nilai p<0,001 maka distribusi bahwa hubungan pengetahuan dan sikap dengan kejadian hipertensi memiliki hubungan yang signifikan.